Association of Anti–Porphyromonas gingivalis Antibody Titers With Nonsmoking Status in Early Rheumatoid Arthritis: Results From the Prospective French Cohort of Patients With Early Rheumatoid Arthritis. Issue 7 (July 2015) - Seror, Raphaèle; Le Gall‐David, Sandrine; Bonnaure‐Mallet, Martine; Schaeverbeke, Thierry; Cantagrel, Alain; Minet, Jacques; Gottenberg, Jacques‐Eric; Chanson, Philippe; Ravaud, Philippe; Mariette, Xavier
<x xml:space="preserve">Abstract</x> Objective To investigate the possible link between Porphyromonas gingivalis infection and rheumatoid arthritis (RA), according to antibody profile, genetic and environmental factors, and RA severity. Methods For assessing P gingivalis infection, serum levels of antibodies directed against P gingivalis lipopolysaccharide were measured in 694 patients with early RA who were not exposed to steroids or disease‐modifying antirheumatic drugs. Anti–P gingivalis antibody titers were compared between patients with early RA and various control groups, and according to various patient characteristics. Results Anti–P gingivalis antibody titers did not significantly differ between patients with RA and controls and did not significantly differ with anti–citrullinated protein antibody (ACPA), rheumatoid factor (RF), or HLA shared epitope status. Anti–P gingivalis antibody titers were significantly higher among patients who had never smoked compared to patients who had ever smoked (P = 0.0049). Among nonsmokers, high anti–P gingivalis antibody levels were associated with a higher prevalence of erosive change (47.5% versus 33.3% with modified Sharp/van der Heijde score erosion subscale ≥1; P = 0.0135). Conclusion In this large early RA cohort, we did not detect any association of anti–P gingivalis antibodies with RA or with ACPA status. These results suggest that the association of periodontitis and RA could be linked to bacterial species other than P gingivalis or to a mechanism other than citrullination. Nevertheless, we found higher anti–P gingivalis antibody titers in nonsmokers. In addition, in this population of nonsmokers, high anti–P gingivalis antibody titers were associated with more severe disease. We hypothesize that the role of tobacco in RA pathogenesis is so high that the effect of P gingivalis could be revealed only in a population not exposed to tobacco.